2001
DOI: 10.1074/jbc.m100180200
|View full text |Cite
|
Sign up to set email alerts
|

The Carboxyl Terminus of Type VII Collagen Mediates Antiparallel Dimer Formation and Constitutes a New Antigenic Epitope for Epidermolysis Bullosa Acquisita Autoantibodies

Abstract: Type VII collagen, the major component of anchoring fibrils, consists of a central collagenous triple-helical domain flanked by two noncollagenous domains, NC1 and NC2. The NC2 domain has been implicated in catalyzing the antiparallel dimer formation of type VII procollagen. In this study, we produced the entire 161 amino acids of the NC2 domain plus 186 amino acids of adjacent collagenous domain (NC2/COL) and purified large quantities of the recombinant NC2/COL protein. Recombinant NC2/ COL readily formed dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
54
1
5

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 34 publications
1
54
1
5
Order By: Relevance
“…Synthesized and secreted by epidermal keratinocytes, type VII procollagen monomers self-assemble into antiparallel dimers, which then associate laterally to form anchoring fibrils Morris et al, 1986). Initial dimer formation and stabilization through disulfide bonding seems to require retention of the type VII procollagen C-propeptide, also known as the NC2 domain (Chen et al, 2001;Lunstrum et al, 1987). However, proteolytic removal of NC2 seems necessary to anchoring fibril formation, as a mutation that eliminates the cleavage site results in the severe blistering disease dystrophic epidermolysis bullosa (Bruckner-Tuderman et al, 1995).…”
Section: Non-fibrillar Collagensmentioning
confidence: 99%
“…Synthesized and secreted by epidermal keratinocytes, type VII procollagen monomers self-assemble into antiparallel dimers, which then associate laterally to form anchoring fibrils Morris et al, 1986). Initial dimer formation and stabilization through disulfide bonding seems to require retention of the type VII procollagen C-propeptide, also known as the NC2 domain (Chen et al, 2001;Lunstrum et al, 1987). However, proteolytic removal of NC2 seems necessary to anchoring fibril formation, as a mutation that eliminates the cleavage site results in the severe blistering disease dystrophic epidermolysis bullosa (Bruckner-Tuderman et al, 1995).…”
Section: Non-fibrillar Collagensmentioning
confidence: 99%
“…Therefore, structural alterations in C7 may result in functional disruption of its interactions with ECM components, leading to the epidermal-dermal separation seen in DEB. We also showed that the NC2 domain and its adjacent triplehelical domain initiate the triple-helical assembly of C7 and catalyze the antiparallel dimer formation of the procollagen C7 (17).…”
mentioning
confidence: 99%
“…The antiparallel dimers then aggregate laterally to form anchoring fibrils which interact with microfibrils, collagen fibrils, and micro-thread-like fibers within the papillary dermis. These interactions are thought to secure the epidermis and its underlying basement membrane zone to the underlying papillary dermis.We have expressed and purified large quantities of recombinant full-length C7 as well as various domains including the NC1 and NC2 domains in human 293 cells (15)(16)(17). Using these recombinant proteins, we carried out extensive structural and functional studies and showed that recombinant C7 is identical to authentic C7 purified from skin cells (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2D). The pro-collagen type VII molecule is a homotrimer of proα1(VII)-chains and each pro-collagen molecule forms an anti-parallel dimer, with a short C-terminal overlap and disulfide-bonding (Chen et al 2001). Finally, dimers aggregate laterally to form the anchoring fibrils.…”
Section: Epithelial Specific Collagens Types VII and Xviimentioning
confidence: 99%